2007
DOI: 10.1007/s10646-007-0172-y
|View full text |Cite
|
Sign up to set email alerts
|

Heavy-metal concentrations in three owl species from Korea

Abstract: This study presents concentrations of heavy metals (iron, zinc, manganese, copper, lead, and cadmium) in livers of three owl species from Korea. Essential trace elements (iron, zinc, manganese, and copper) did not differ among the owl species. We suggest that the essential elements are within the normal range and are maintained by normal homeostatic mechanisms. Lead and cadmium concentrations in Eurasian Eagle Owls (Bubo bubo) were significantly lower than in Brown Hawk Owls (Nixos scutulata) and Collared Scop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 59 publications
0
7
1
Order By: Relevance
“…Further levels of Zinc reported by Kim et al, (2008) in Brown Hawk Owl Korea are higher than the levels presently reported. However, impact of Zn on White-backed Vulture is unclear.…”
Section: Resultscontrasting
confidence: 71%
“…Further levels of Zinc reported by Kim et al, (2008) in Brown Hawk Owl Korea are higher than the levels presently reported. However, impact of Zn on White-backed Vulture is unclear.…”
Section: Resultscontrasting
confidence: 71%
“…The Cd concentrations in the kidneys of most wild freshwater ducks, which are the primary prey of the studied species, are relatively high, i.e., 2–8 (Scheuhammer 1987 ; Binkowski et al 2013 ), and Cd bioaccumulation is accompanied by changes in the levels of some essential elements, including Zn (Brzoska and Moniuszko-Jakoniuk 2001 ), which was reflected in our study in the significantly high correlation between both elements ( r s = 0.75). Positive correlations between tissue concentrations of Cd with Zn have been reported for many species of birds (Furness 1996 ; Nam and Lee 2006 ; Kim et al 2008 , 2009 ). Increased liver concentrations of Zn (Chmielnicka et al 1989 ; Lopez-Alonso et al 2002 ) decrease the availability of this element for other tissues (for example, bone) and many biochemical processes (Brzoska and Moniuszko-Jakoniuk 2001 ), but an increased Zn supply may reduce Cd absorption and accumulation, thus preventing or reducing the adverse actions of Cd.…”
Section: Discussionmentioning
confidence: 88%
“…As biomonitoring sentinels, raptors can provide early warnings of the potential impacts of contaminants on humans and the environment and can act as a means of tracking the success of associated mitigation measures (Kim et al 2008 ; Ansara-Ross et al 2013 ; Gomez-Ramírez et al 2014 ). The value of birds as biomonitors of environmental pollution has been widely recognized (Horai et al 2007 ; Schummer et al 2011 ; Kim and Oh 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, climate changes, groundwater withdraw, decreasing food reserves, and the presence and persistence of the contaminants still pose a serious threat to the inhabitants of the protected ecosystems (Deguise and Kerr 2006;Greenwald and Bradley 2008;Powles et al 2000;Turner et al 2006). The pesticides in the water and sorbed to sediments can be consumed directly or after they have been accumulated in plant matter (Celik et al 2006;Gjershaug et al 2008;Kim et al 2008b). Research has shown that birds that ingested organochlorines exhibited abnormal reproductive behavior, thinning of shells, feminization of males, and immunotoxicologic responses (Cid et al 2007;Harris et al 2005).…”
Section: Contamination Levels and Impacts In Other National Parksmentioning
confidence: 99%